2003
DOI: 10.1177/106591290305600404
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Setting in Congressional Elections: The Impact of Issues and Campaigns on Voting Behavior

Abstract: Do issues matter? This article extends recent research on issue voting and campaign agenda-setting to voting decisions in congressional elections. We use a unique data set that includes information from a survey of candidates and campaign aides who competed in the 1998 House elections and a survey of individuals who voted in them. The study assesses the impact of campaign-specific variables on citizens’ voting decisions, while controlling for relevant attitudinal and demographic factors. We find that when a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 40 publications
(29 reference statements)
2
27
0
2
Order By: Relevance
“…Short-term voter coalitions, holding a particular interest in selected policy issues, appear to take over the stable body of electors. Moreover, as empirical studies point out, independent voters are more likely to be affected by policy issues than partisan voters are (Abbe et al 2003). This increases the number of voters who are prone to base their candidate evaluation on considerations raised in policy debates.…”
Section: The Economic Theory Of Democracy and The Tactical Role Of Thmentioning
confidence: 93%
See 1 more Smart Citation
“…Short-term voter coalitions, holding a particular interest in selected policy issues, appear to take over the stable body of electors. Moreover, as empirical studies point out, independent voters are more likely to be affected by policy issues than partisan voters are (Abbe et al 2003). This increases the number of voters who are prone to base their candidate evaluation on considerations raised in policy debates.…”
Section: The Economic Theory Of Democracy and The Tactical Role Of Thmentioning
confidence: 93%
“…4 The very point of departure is the assumption that voters support those political actors whose party is perceived as competent in handling issues that dominate public debate. Consequently, politicians highlight dimensions within which they have the advantage, that are consistent with their party reputation (Simon 2002;Abbe et al 2003). In contrast, politicians avoid emphasizing issues that do not play to their individual or party strengths or that favor the opposing party.…”
Section: The Emergence Of the Political Agenda: The Three Steps Of Thmentioning
confidence: 94%
“…Abbe et al (2003) found that voters are more likely to support candidates whom they consider competent on their issues. These findings suggest that candidates need to build voters' competence on these issues by proposing a well-defined agenda, and that the candidates must use their campaign to emphasize problems and solutions on these issues.…”
Section: Propositionmentioning
confidence: 96%
“…Furthermore, Iyengar and Valentino (2000) found that Republicans watching ads from the 1996 presidential election rated Dole's ads more informative when they focused on Republican rather than Democratic issues, while Democrats preferred Clinton's ads on Democratic issues. And Abbe et al (2003) found that when a candidate and a voter had the same top issue, the candidate was more likely to get that vote if the issue was one the candidate's party owned. But voters may wish to field a candidate who can compete with the general election opponent on issues that their own party does not own.…”
Section: Issue Ownershipmentioning
confidence: 98%